THE INFLUENCE OF PRODUCT QUALITY ON CONSUMER LOYALTY THROUGH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) - Murti Sari Dewi; Muji Rahayu (RADJA PUBLIKA, 2026)
This study analyzes the effect of product quality on customer loyalty through Customer Relationship Management (CRM) as a mediating variable at Company X in Cimahi City. A quantitative approach was employed using purposive sampling with 70 respondents. Data were collected through a questionnaire using a five-point Likert scale. The data were processed and analyzed using the SPSS plug-in Process Macro Hayes Model 4. The hypothesis testing results show that product quality has a positive effect on CRM, and product quality also has a positive effect on customer loyalty, although the effect is not significant. Meanwhile, CRM has a positive and significant effect on customer loyalty and mediates the relationship between product quality and customer loyalty. These findings highlight the important role of CRM in strengthening the relationship between product quality and customer loyalty.